Tepian Sungai Tallo Sebagai Kampung Wisata Di Kota Makassar - Nur Iqbal; Irma Rahayu; Safruddin Juddah (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2022)
One of the slum areas in Makassar City is Sengkabatu Village which needs to be optimized for settlement arrangement. This is expected to improve society's economic and social sectors by the 2015-2034 Makassar City Spatial Plan. This area is included in the strategic space from the point of view of functional importance and environmental carrying capacity for the development, improvement, consolidation, and rehabilitation of the Tallo River strategic area. Residential issues are also inseparable from the life of the people of Sengkabatu Village. Therefore the design of a growing house is one of the ideas for housing problems on limited land where this growing house grows based on the needs of residents. The people of Sengkabatu Village also hope that there will be changes in the arrangement of the village that do not only focus on the construction sector. The concept of a Tourism Village, which focuses on water tourism, culinary tourism, and village tourism is one of the ideas which can be a plan that can improve the quality of life of the Sengkabatu people and improve the Tallo River ecosystem.